Consistent patterns in the inconsistent associations of Insulin-like growth factor 1 (IGF-1), C-Reactive Protein (C-RP) and Interleukin 6 (IL-6) levels with delirium in surgical populations. A systematic review and meta-analysis. (November 2021) - Adamis, Dimitrios; van Gool, Willem A.; Eikelenboom, Piet
Highlights: Despite the phenomenologically inconsistent results there is an underling consistent association of serum I-GF1, C-RP and IL-6 with postoperative delirium which is dependent on the examined samples. Low levels of IGF-1 are significantly associated with post-operative delirium in abdominal surgical samples. High levels of C-RP are associated with delirium in acute orthopaedic and elective abdominal operations. Hight levels of IL-6 seems a consistent predictor for delirium in surgical samples. Those similar patterns may reflect different underling mechanisms in delirium and different predisposing factors. Abstract: Background: Biomarkers for delirium could increase diagnostic accuracy and may help to identify pathological pathways. Until now study findings concerning cytokine levels have been inconsistent. Aims: Systematic review and meta-analysis investigating the association between peripheral levels of Insulin-like Growth Factor-1 (IGF-1), C-Reactive Protein (C-RP) and Interleukin-6 (IL-6) and delirium in surgical patients, and to explore if there are distinct/specific patterns that may potentially explain inconsistent results. Methods: PubMed, Scopus, CINAHL, Cochrane, and EMBASE databases were searched. Inclusion criteria were: prospective studies, surgical populations excluding preoperative delirium, available data. The following were collected: type of operation (orthopaedic, abdominal, etc), the timing of operation (acute, elective, both), demographics, number of participants with delirium, time of preoperative blood withdrawal, and preoperative levels of each biomarker. Results: Low levels of IGF-1 (n = 7 studies) are significantly associated with post-operative delirium in abdominal surgical samples. High levels of C-RP (n = 9) are associated with delirium in acute orthopaedic and elective abdominal operations. IL-6 (n = 14) is a significant predictor of post-operative delirium in a variety of surgical conditions (elective or acute). Discussion: A common pattern exists in the otherwise conflicting reported findings. This similarity may reflect different underling mechanisms and predisposing factors like cachexia and catabolic stages. It seems that delirium in abdominal surgery is triggered by IGF-1 disturbances, while in other surgeries by an inflammatory reaction. Conclusions: Despite the contradictory results concerning the association of IGF-1, C-RP and IL-6 with postoperative delirium, the present meta-analysis shows that there are certain patterns. IL-6 seems a consistent predictor for delirium in surgical samples.